2015
DOI: 10.1111/aab.12219
|View full text |Cite
|
Sign up to set email alerts
|

Hexaploid wheat (Triticum aestivum) root miRNome analysis in response to salt stress

Abstract: Hexaploid bread wheat (Triticum aestivum) is one of the major crops grown and consumed all over the world. Elevated soil salinity causes reduction in crop yield and quality; therefore, several strategies were developed to improve salt-tolerant cultivars. MicroRNAs (miRNAs), small and non-coding RNAs, regulate gene expression at post-transcriptional level and play important roles in stress tolerance. Here, we used a broad-range miRNA-microarray analysis to investigate the root-miRNA profiles of two cultivars, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 32 publications
3
33
0
1
Order By: Relevance
“…In fact, this reduction of crop yield has been influenced by many environmental factors. Among these factors, salinity is one of the major causes for the yield reduction [54,55]. A similar result was found in these study locations where 92 percent of the cropping area is affected by the salinity problem.…”
Section: Effect Of Salinity On Fish Species Productionsupporting
confidence: 79%
“…In fact, this reduction of crop yield has been influenced by many environmental factors. Among these factors, salinity is one of the major causes for the yield reduction [54,55]. A similar result was found in these study locations where 92 percent of the cropping area is affected by the salinity problem.…”
Section: Effect Of Salinity On Fish Species Productionsupporting
confidence: 79%
“…In the context of in silico identification of miRNAs target genes, we found that 100 PvbHLH genes targeted by 86 plant miRNAs. One of the identified miRNA was miR396, which was previously reported for salt stress response (Liu et al 2008;Eren et al 2014). In addition to the targeting of salt responsive genes, this family of miR-NAs also target growth regulating factor (GRF) transcription factors, rhodenase-like proteins, and kinesin-like protein B.…”
Section: Discussionmentioning
confidence: 98%
“…Up to date, several plant miRNAs have shown to play roles in abiotic and biotic stress responses (Sunkar and Zhu 2004;Lu et al 2005;Lu and Huang 2008;Eldem, et al 2012;Eldem, et al 2013;Inal, et al 2014;Eren, et al 2015;Hajyzadeh, et al 2015). For example, plant miRNAs are involved in adaptation to nutrient deficiency (Fujii et al 2005), drought (Zhao, et al 2007;Liu et al 2008;, cold (Miura and Furumoto 2013), mechanical stress (Lu, et al 2005), bacterial or fungal stress (Navarro et al 2006;Inal, et al 2014), and salinity (Sunkar et al 2008;Inal, et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…genes at post-transcriptional level (Gupta et al 2014). In recent years, several studies showed that miRNAs are involved in response to abiotic stress (Sunkar et al 2007;Lu and Huang 2008;Zhou et al 2010;Eldem et al 2012;Wang et al 2013;Eren et al 2015;Hajyzadeh et al 2015). Several miRNA families have been reported to be differentially regulated in response to drought stress in various plant species, including rice (Zhao et al 2007), tomato (Solanum lycopersicum , Arabidopsis (Liu et al 2008), Medicago truncatula (Trindade et al 2010), peach (Eldem, et al 2012), barley (Kantar et al 2010), and wheat (Gupta, et al 2014;Pandey, et al 2014).…”
Section: Introductionmentioning
confidence: 99%